2021
DOI: 10.1016/j.ijpddr.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Antiamoeboid activity of squamins C–F, cyclooctapeptides from Annona globifora

Abstract: Free-living amoebae of Acanthamoeba spp. are causative agents of human infections such as granulomatous amoebic encephalitis (GAE) and Acanthamoeba keratitis (AK). The exploration of innovative chemical entities from natural sources that induce intrinsic apoptotic pathway or a Programmed Cell Death (PCD) in Acanthamoeba protozoa is essential to develop new therapeutic strategies. In this work, the antiamoeboid activity of squamins C–F ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The cysticidal activity was evaluated by the alamarBlue® assay at 168 h and confirmed visually by inverted microscopy. Cysts of the Acanthamoeba strains were obtained as it has been described before [42,43]. First, 50 μL of 5⋅10 4 cysts/mL, as final concentration of mature cysts of Acanthamoeba strains, were cultivated in PYG medium in triplicate on a 96-well plate with 50 μL of serial dilutions of meroterpenes gongolarones A (1), C (3), and cystomexicone B (4).…”
Section: In Vitro Effect Against Of Acanthamoeba Spp Cystsmentioning
confidence: 99%
“…The cysticidal activity was evaluated by the alamarBlue® assay at 168 h and confirmed visually by inverted microscopy. Cysts of the Acanthamoeba strains were obtained as it has been described before [42,43]. First, 50 μL of 5⋅10 4 cysts/mL, as final concentration of mature cysts of Acanthamoeba strains, were cultivated in PYG medium in triplicate on a 96-well plate with 50 μL of serial dilutions of meroterpenes gongolarones A (1), C (3), and cystomexicone B (4).…”
Section: In Vitro Effect Against Of Acanthamoeba Spp Cystsmentioning
confidence: 99%
“…In general terms, the combined results of the adulticidal and larvicidal activity indicated that the methanolic extracts of Annona globiflora, Annona scleroderma, Litchi chinensis and Azadirachta indica have the best effectiveness. Annona genus has become a prolific producer of interesting compounds with great biological activity (36,37) . The acaricidal activities of the extracts of A. globiflora and A. scleroderma are possibly related to the presence of acetogenins, the main chemical constituents of the Annonaceae family, which have been found to have potent pesticidal activity against a variety of arthropods (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Squamins C–F were isolated from the seeds of A. globifora and tested in vitro against trophozoites of Acanthamoeba spp. strains such as A. castellanii Neff, A. polyphaga , A. griffin and A. quina ( Table 8 ) [ 200 ]. All tested compounds exhibited antiamoeboid activity against the strains by inducing programmed cell death [ 200 ].…”
Section: Pharmacological Activity Of Isolated Compounds From ...mentioning
confidence: 99%
“…strains such as A. castellanii Neff, A. polyphaga , A. griffin and A. quina ( Table 8 ) [ 200 ]. All tested compounds exhibited antiamoeboid activity against the strains by inducing programmed cell death [ 200 ]. The same compounds were also tested for their cytotoxicity against murine macrophage cell line J774A.1 (ATCCTIB-67) and showed no cytotoxicity effect with CC 50 values greater than 200 μM [ 200 ].…”
Section: Pharmacological Activity Of Isolated Compounds From ...mentioning
confidence: 99%